Molar pregnancy with a coexisting live fetus as a challenge for perinatology. A mini-review with two case reports - Ciebiera, Michał; Wojtyła, Cezary; Jakiel, Grzegorz; Roszkowski, Tomasz (Journal of Health Inequalities, 2018)
Coexistence of a molar pregnancy with a live fetus is a rare and complex clinical condition. Twin pregnancies with a healthy fetus and a hydatidiform mole arise in one in 20,000-100,000 pregnancies, depending on data. This article reviews available literature on pregnancies with coexistence of a hydatidiform mole and a live fetus, and presents two case reports. Successful diagnosis is based on multiple elements e.g. experience in sonography and prenatal diagnosis. There are no clear guidelines for how to proceed with this pathology, therefore the management strategies remain uncertain. Parents must be aware of increased risk of intrauterine fetal growth restriction, fetal distress, premature labor, preeclampsia, thyrotoxicosis, hemorrhage, and gestational trophoblastic neoplasia associated with this condition. Management in these pregnancies depends on the individual expectation of the pregnant woman, and parents should be made aware of the low probability of favourable outcome for the fetus. A large case series of molar pregnancies with a coexisting live fetus could be useful to establish evidence-based management guidelines.